2004
DOI: 10.1108/02635570410561645
|View full text |Cite
|
Sign up to set email alerts
|

Performance observation and analysis of an information re‐engineered supply chain: a case study of an automotive firm

Abstract: This paper provides an empirical illustration of the potential of a cross‐supply chain information system (CSCIS) in an automotive industry setting. Whilst dramatic reductions in downstream finished goods, work‐in‐progress and raw materials inventories have taken place in many automotive supply chains, this paper looks at how demand information can be made more transparent in order to improve the efficiency of upstream operations. The paper concentrates on the findings from a case study that used a prototype I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Although for every business the nancial performance is the ultimate goal but external integration impacts on other indicators such as innovation performance of SMEs as well (Llorens et al, 2003), non-financial performance and market share (Demirbag et al, 2006). The external integration enhances productivity and increases market share of SMEs businesses (Li et al, 2006;Lyons et al, 2004;Tan et al, 1998). Thus, based on available literature that provide evidence regarding importance of external integration for firm's success, this paper argues that external integration plays a role of moderator in the relationships between entrepreneurial competencies and business success.…”
Section: Resource Dependence Theory (Rdt) and External Integrationmentioning
confidence: 99%
“…Although for every business the nancial performance is the ultimate goal but external integration impacts on other indicators such as innovation performance of SMEs as well (Llorens et al, 2003), non-financial performance and market share (Demirbag et al, 2006). The external integration enhances productivity and increases market share of SMEs businesses (Li et al, 2006;Lyons et al, 2004;Tan et al, 1998). Thus, based on available literature that provide evidence regarding importance of external integration for firm's success, this paper argues that external integration plays a role of moderator in the relationships between entrepreneurial competencies and business success.…”
Section: Resource Dependence Theory (Rdt) and External Integrationmentioning
confidence: 99%
“…In a study using data on the automotive, electronics, and aircraft industries, Kros, Falasca, and Nadler (2006) also discovered potential inventory reductions for suppliers of OEMs through the use of JIT. Along similar lines, Cachon (2001) and Lyons, Coleman, Kehoe, and Coronado (2004) suggested that supply chain information systems and buyer–supplier coordination programs (e.g., vendor‐managed inventory) could be key drivers in the reduction of inventories. Indeed, Cachon and Olivares (2010) found that integrative manufacturing designs, efficient production, and proactive supply management all have contributed to superior finished goods inventory performance in automotive supply chains.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…SCM often refers to a process-oriented management approach to sourcing, producing, and delivering goods and services from supplier's supplier to customer's customer; these efforts include order management, distribution across all channels, and delivery to customers (Harland, 1996;Lummus et al, 2001 andLamber, 2000). According to Sundram et al (2011), Li et al (2006), and Lyons et al (2004, the shortterm objectives of SCM are enhancement of productivity and reduction of inventory and lead time, and its long-term objectives are to increase market share and to promote integration.…”
Section: Figurementioning
confidence: 99%